Prism Inside: Spectroscopic and Magnetic Properties of the Lanthanide(III) Chloride Oxidotungstates(VI) Ln3Cl3[WO6] (Ln = La – Nd, Sm – Tb) - Dorn, Katharina V.; Blaschkowski, Björn; Förg, Katharina; Netzsch, Philip; Höppe, Henning A.; Hartenbach, Ingo (Zeitschrift für anorganische und allgemeine Chemie (1950), 2017)
The lanthanide(III) chloride oxidotungstates(VI) with the formula Ln3Cl3[WO6] for Ln = La – Nd, Sm – Tb were synthesized by solid‐state reactions utilizing the respective lanthanide trichloride, lanthanide sesquioxide (where available), and tungsten trioxide together with lithium chloride as flux. The title compounds crystallize hexagonally in space group P63/m (no. 176, a = 941–909, c = 543–525 pm, Z = 2). The structures comprise crystallographically unique Ln3+ cations surrounded by six O2– and four Cl– anions (C.N. = 10) forming distorted tetracapped trigonal prisms as well as rather uncommon trigonal prismatic [WO6]6– units, whose edges are coordinated by nine Ln3+ cations. Thus, a 3∞{([WO6]Lne9/3)3+} framework (e = edge‐sharing) is created, which contains tube‐shaped channels along [001] lined with chloride anions. To elucidate the spectroscopic and magnetic properties of the obtained pure phase samples, single‐crystal Raman (for Ln = La – Nd, Sm–Tb), diffuse reflectance (for Ln = La, Pr, Nd, Gd), and luminescence spectroscopy (for bulk Ln3Cl3[WO6] (Ln = La, Eu, Gd, Tb) and Eu3+‐ or Tb3+‐doped derivatives of La3Cl3[WO6] and Gd3Cl3[WO6], respectively) were performed and their temperature‐dependent magnetic moments (for Ln = Pr, Nd, Gd) were determined.